Osmium Polypyridyl Complexes and Their Applications to Dye‐Sensitized Solar Cells. Issue 2 (13th January 2015) - Swetha, T.; Reddy, K. Raveendranath; Singh, Surya Prakash
Abstract Dye‐sensitized solar cells (DSSCs) have received much attention in recent years owing to their efficient conversion of sunlight to electricity. DSSCs became successful alternatives to silicon photovoltaic devices by virtue of their low fabrication costs and easy preparation methods. In DSSCs the dye plays the key role. This review summarizes the applications of osmium sensitizers in DSSCs. We also briefly discussed their synthesis and the effect of various electrolyte systems on device efficiencies.